2013
DOI: 10.1111/j.1365-4632.2012.05846.x
|View full text |Cite
|
Sign up to set email alerts
|

Ear, nose, and throat involvement in Egyptian patients with pemphigus vulgaris: a step towards a better management

Abstract: Full ENT examination as a routine for all patients with PV could be of great value, as it would lead to more accurate diagnosis, therefore improved management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…Furthermore, it is difficult to use symptoms alone to differentiate between CS subtypes, such as CS with nasal polyps and CS without nasal polyps [15]. Sometimes, ENT disorders are linked with other systemic illness like pemphigus vulgaris [16]. For Bangladesh, it may be important to consider ENT problems related to zoonotic diseases [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is difficult to use symptoms alone to differentiate between CS subtypes, such as CS with nasal polyps and CS without nasal polyps [15]. Sometimes, ENT disorders are linked with other systemic illness like pemphigus vulgaris [16]. For Bangladesh, it may be important to consider ENT problems related to zoonotic diseases [17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, concomitant bacterial or fungal infection may lead to mucosal inflammation and contribute to NT symptoms. In line with this, positive bacterial and/or fungal cultures have been reported in 18–37% of patients . Therefore, the sum of all these factors might explain why the severity of mucosal involvement is not always a reflection of overall disease severity in PV, nor is it not related to the type of PV …”
Section: Nt Involvement In Pvmentioning
confidence: 81%
“…An interesting question is whether endoscopic procedures in PV should be performed in both symptomatic and asymptomatic patients. While several studies confirm a significant association between nasal and pharyngeal symptoms with involvement of these anatomical areas, such an association is lacking between laryngeal symptoms and presence of lesions in larynx (Table ). Therefore, we believe endoscopic procedures should be performed in all PV patients, regardless of whether they present NT symptoms or not …”
Section: Nt Involvement In Pvmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 31 different citation hits related to the terms used in the electronic literature search were retrieved. After critical screening of titles, abstracts and full text, 13 articles with a total of 3046 patients with pemphigus, conducted in 10 countries, were suitable in this review . The characteristics of each individual study associated with cigarette smoking and pemphigus are shown in Table .…”
Section: Resultsmentioning
confidence: 99%